The images and realities of foreign top professionals in Finnish working and living environments - Mika Raunio (European Regional Science Association (ERSA), 2002)
In the immediate future foreign labour will play an increasingly important role in the competitiveness of expertise-intensive firms and whole urban regions in Finland as has already happened in many other western countries in recent years. Due to high birth rates at the late 1940s and the early 1950s compared with almost half smaller birth rates in the early 1970s the number of retiring people will increase dramatically in relation to people entering the labour market. Labour shortage may be eased by educational reforms and by raising the age of retiring from the labour force, but one crucial part of the solution is foreign labour that should fill in the gap in the Finnish labour markets. At the moment labour shortage is visible in only some branches of the fastest growing industries and the slowing world economy fades the visibility of even these shortages. However, the fast growth of economy in previous years gave the first ideas about the attractiveness of Finland due to labour shortage mainly in the information technology related business. Professionals from around the world came to fill this rather strictly determined gap on skills. This study aims at a profound understanding of key issues in attracting and retaining foreign professionals in Finnish working and living environments. Although this study focuses on professionals in IT-industry, it shoul provide a wider picture of Finland and its industries abilities to attract labour force in immediate future. (project still running untill June 2002)
Keywords: 330